Volumetric Analysis of a Novel Chimeric Gracilis and Profunda Artery Perforator Flap - Van Spronsen, Nicole R.; Hammond, Jacob B.; Plonkowski, Alexander T.; Jokerst, Clint E.; Flug, Jonathan A.; Shrout, Max A.; Reece, Edward M.; Casey, William J., III; Rebecca, Alanna M. (Journal of Reconstructive Microsurgery, 2024)
Background The presence of a chimeric gracilis and profunda artery perforator (PAP) flap with a common arterial pedicle has been demonstrated on computed tomography angiography in up to 59% of patients and confirmed in a cadaveric model. Already utilized for head and neck reconstruction by Heredero et al, this novel flap could provide more volume than either flap alone which is advantageous, particularly in patients with sizable defects. The purpose of this study was to determine the average tissue volume that can be utilized from this chimeric flap.Methods CT Angiogram imaging studies exhibiting chimeric flap anatomy were reviewed over a 7-year period at a single institution utilizing Visage Version 7.1, a radiology picture archiving and communication system. This software was used to trace the flap pedicles and to capture estimated soft tissue volumes of each respective flap.Results A total of 31 patients, consisting of 52 lower extremity gracilis and PAP chimeric flaps, underwent tissue volume analysis. The average total volume of soft tissue supplied by the gracilis flap was found to be 70.21 cm3 (standard deviation [SD] = 26.99). The average volume of the PAP flap was 31.73 cm3 (SD = 26.12). The average total volume captured by the chimeric gracilis and PAP flap was 101.94 cm3 (SD = 62.40).Conclusion The potential soft tissue volume that can be harvested from a chimeric gracilis and PAP flap is significantly greater than solitary gracilis or PAP flaps. This chimeric flap may serve as a viable and advantageous reconstructive option for patients requiring large volume soft tissue coverage, particularly if other sizable options are not available.
Keywords: reconstruction; lower extremity; gracilis; profunda artery perforator; microsurgery